Experimental Study on Viscoplastic Property of Unsaturated Reticulate Red Clay Used as an Engineered Barrier - Chuang Zhang; Jian-Zhong Li; Yong He (Geofluids)
In this study, to explore the feasibility of a compacted red clay as an engineered barrier in landfills, the viscoplastic property of remodeled unsaturated reticulate red clay was studied through a series of triaxial tests. According to the deviatoric stress–axial strain curves obtained through loading tests with varying strain rates and under different conditions, the viscoplastic parameter β of remodeled reticulate red clay was obtained. The effects of different matric suctions and net confining pressures on the viscoplasticity of unsaturated reticulate clay were analyzed. The test results showed that remodeled reticulate red clays with different degrees of saturation have similar viscoplastic properties, and their stress–strain curves are all isotach. The stiffness of unsaturated reticulate red clay increased with increasing confining pressure and matric suction. The relationship between β and the net confining pressure can be described using a linear equation. The β value of the specimens increased with increasing matric suction under a constant net confining pressure. A similar linear relationship was observed between β and the matric suction. These relationships are explained considering the loading rate effect mechanism.